PENDIDIKAN TERPADU DAN PENGEMBANGAN KREATIVITAS - Nanang Nuryanta (EL-TARBAWI, 2002)
The concept of the integrated education emerges can be regarded as a process to discover the profile of ideal education. Actually, the term focusing on how to form the model of education that combining various aspects of potentials of learners. The aspects involve the cognition, affection, psychomotor, and the combination among the talent" environmental cultures, and social system. According to the author, that the developing learners' creativity can be conducted as well as possible if there is a conducive situation in education institution. In this respect, the creativity will increase if there is a harmony and conducive interaction between individual personal and his/her environment. For that reason, the ideal education process can produce outcomes who have character, Islamic Civilization, and mastering science and technology constitutes collective responsibility of school, family, and society. In brief, the education is a process and human investment how to produce a qualified human resources.